Investigating The Combined Effects of Replacing Cement with Sugarcane Bagasse Ash and Coarse Aggregate with Ceramic Tile Waste in Concrete Production - Jumani, Sajjad Hussain; Mangi, Sajjad Ali; Phul, Najeeb-ur-Rehman; Faiz, Rizwanullah (Journal of Structural Monitoring and Built Environment, 2023)
The aim of this study is to elevate the effects of combine inclusion of Sugarcane Bagasse Ash (SCBA) as cement and ceramic tile waste (CTW) as coarse aggregate replacement on concrete properties. However, SCBA is a waste material and having good pozzolanic properties. The importance of sustainability and recycling has become increasingly recognized and understood in academia and industry over the last several decades. Besides that, the recycling construction waste and debris is one of many avenues that provide a great opportunity to reduce the construction industry reliance on decreasing natural resource supplies. In order to optimize the percent replacement of cement by SCBA, the cement has been partially replaced by SCBA constant, the ceramic waste is replaced at the dosages 10%, 20% and 30% by weight of coarse aggregates. The various outcomes of replacement by SCBA and CTW have been analyzed through evaluation of different properties like workability and compressive strength for 7?days and 28?days. The results further revealed that the workability decreased with the inclusion of SCBA and CTW. The compressive Strength of concrete mix was relatively higher at 10% replacement of cement by SCBA and 10% replacement of CTW, after which it decreased beyond 10% replacement. The maximum compressive strength was observed as 26.57 N/mm2 SCBA in proportion of constant 10% by weight in concrete mixes. It was deduced from the outcomes of this study that 10% SCBA and 10% CTW replacement by cement and coarse aggregates respectively could be considered as optimum replacement.